2024
DOI: 10.3390/v16010102
|View full text |Cite
|
Sign up to set email alerts
|

Timely Monitoring of SARS-CoV-2 RNA Fragments in Wastewater Shows the Emergence of JN.1 (BA.2.86.1.1, Clade 23I) in Berlin, Germany

Alexander Bartel,
José Horacio Grau,
Julia Bitzegeio
et al.

Abstract: The importance of COVID-19 surveillance from wastewater continues to grow since case-based surveillance in the general population has been scaled back world-wide. In Berlin, Germany, quantitative and genomic wastewater monitoring for SARS-CoV-2 is performed in three wastewater treatment plants (WWTP) covering 84% of the population since December 2021. The SARS-CoV-2 Omicron sublineage JN.1 (B.2.86.1.1), was first identified from wastewater on 22 October 2023 and rapidly became the dominant sublineage. This cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It rapidly spread in the following weeks to most regions (Espinosa-Gongora et al, 2023). Genomic monitoring of SARS-CoV-2 in Berlin's wastewater identified JN.1 as early as September 2023 using an Illumina COVIDSeq Test (Bartel et al, 2024). Results from wastewater surveillance sequencing in Denmark, indicated that the BA.2.86 variant was circulating in the country at a low level in mid-August (Rasmussen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It rapidly spread in the following weeks to most regions (Espinosa-Gongora et al, 2023). Genomic monitoring of SARS-CoV-2 in Berlin's wastewater identified JN.1 as early as September 2023 using an Illumina COVIDSeq Test (Bartel et al, 2024). Results from wastewater surveillance sequencing in Denmark, indicated that the BA.2.86 variant was circulating in the country at a low level in mid-August (Rasmussen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The use of wastewater monitoring can provide a comprehensive approach to tracking the circulation and spread of different SARS-CoV-2 variants within a community or population (Bartel et al, 2024;Combe et al, 2024;Cutrupi et al, 2022;Espinosa-Gongora et al, 2023;Lipponen et al, 2024). This method provides a broader perspective beyond individual testing, offering insights into the overall viral landscape and aiding in the early detection of emerging variants (Sapoval et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sotrovimab serum half-life was improved by inserting the Met428Leu/Asn434Ser (LS) mutation (Xtend TM ) in the Fc region. Unlike with other half-life extended anti-Spike mAbs, this mutation does not impact the ADCC functions of sotrovimab, which are important for its activity against SARS-CoV-2 [ 7 , 8 , 9 ]. This mutation was previously used in the mAb ravulizumab (approved for paroxysmal nocturnal hemoglobinuria).…”
Section: Introductionmentioning
confidence: 99%